Effects of traffic composition on noise generated by typical Brazilian roads - Lenzi, A.; Filho, J.M. A.; Zannin, P.H. T. (Archives of Acoustics, 2003)
The effects of traffic composition on the noise generated by typical Brazilian roads are analyzed in this work Composition is defined as the percentage of heavy vehicles (trucks and buses) with respect to the overall number of vehicles. Noise measurements were made at 10 m from lane edges of three typical roads at the city of Florianópolis, SC. All sites had indentical characteristics, such us, long and horizontal straights, free of reflections from buildings and walls, traffic flowing average speed of 80 km/h, and distant from traffic lights and round abouts. Measurements were made on the same days of the week and at the same time (from 06:00 to 10:10 h). On these three roads a total of 149 measurements were made and for each of them the percentile level L10 and the equvalent level Leq were calculated. These levels were plotted against the composition of the traffic from which were obtained empirical expressions, with reasonably good correlation indexes, which can be used for predicting road traffic noise levels based on the knowledge of traffic parameters. Information obtained in this work will help authorities to foresee the response of communities to typical Brasilian road traffic noise. Keywords: Road traffic noise, Vehicle Noise, Community Noise, Traffic Volume Composition.